Review : Potensi Aktivitas Anti Virus Dari Produk Alami Lebah Kelulut - Batistuta, Muhammad Alib; Aulia, Annisa; Kustiawan, Paula Mariana (Jurnal Farmasi Udayana; Vol. 10, No 2, Tahun 2021DO - 10.24843/JFU.2021.v10.i02.p06, 2021)
Up to present, many deadly diseases are caused by viral infections. Herbal therapy is a preventive effort made by the community to overcome diseases that come from viruses. Antiviral drug resistance is also the reason people consume herbs from natural ingredients. One of the natural products has the potential to come from kelulut bee products consisting of propolis, pollen, and honey. The kelulut bee or stingless bee is a type of bee that is commonly found in countries with tropical climates such as Indonesia, but there is still little scientific information that examines its potential as an antiviral. This study aims to analyze data on the potential antiviral activity of kelulut bee products through the collection of related articles. The research conducted is a literature review, so the research method is carried out by collecting related articles using search engines such as NCBI, Sciencedirect, and Google Schoolar. Kelulut bee products such as propolis, pollen and honey have potential pharmacological activity as antiviral. This anti-viral activity is due to the presence of compounds such as alkaloids, flavones, apigenin derivatives and other compounds which will be discussed further. Natural products from kelulut bees have potential as an alternative to antiviral therapy. It is also recommended to conduct more in-depth research on the potential of kelulut bee natural products to obtain these therapeutic products.